Framing food waste: development and evaluation of a science communication format at the workplace - Nigg, Stefanie; Kandut, Rebecca; Serong, Julia; Déchène, Monica; Veselá, Kateřina; Klinger, Carmen (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
The mitigation of the climate crisis demands effective communication strategies. Transforming food systems plays a key role in climate protection, not only by changing eating habits, but also by preventing food waste. While workplaces are commonly used for health promotion activities, they are a rare setting for science communication. This practice insight targets individual food waste reduction through a workshop at the workplace, including a lunch from rescued food, documentary screening, discussion, and expert presentation. It aimed to enhance participants’ self-efficacy and intention to reduce food waste. The effectiveness of the screening was tested experimentally by evaluating the effects of positive and negative framing. Exposure to negative framing was associated with higher intensity in negative affect, whereas positive framing appeared to be associated with higher self-efficacy. Furthermore, this practice insight provides strategies to foster science communication in workplaces.
Keywords: Bridging Research; Environmental Communication